2020
DOI: 10.1136/esmoopen-2019-000592
|View full text |Cite
|
Sign up to set email alerts
|

The sarcoma diagnostic interval: a systematic review on length, contributing factors and patient outcomes

Abstract: Sarcomas are rare and heterogeneous mesenchymal tumours of soft tissue or bone, making them prone to late diagnosis. In other malignancies, early diagnosis has an impact on stage of disease, complexity of therapeutic procedures, survival and health-related quality of life (HRQoL). Little is known about what length of diagnostic interval should be considered as delay in patients with bone (BS) or soft tissue sarcomas (STS). To quantify total interval (defined as time from first symptom to histological diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 78 publications
2
82
0
2
Order By: Relevance
“…Another possible explanation would be that the rarity of GIST at the YA age leads to a delay in (correct) diagnosis. Delay of diagnosis in sarcomas, especially at this age, remains a problem, and efforts to educate doctors and patients should be continued [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation would be that the rarity of GIST at the YA age leads to a delay in (correct) diagnosis. Delay of diagnosis in sarcomas, especially at this age, remains a problem, and efforts to educate doctors and patients should be continued [35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature review, sex, age at diagnosis, SES, histology, stage of disease, tumor grade, and localization were selected as independent variables. 4 In the case of multicollinearity, we tried both factors in different models. The factor that resulted in the best model was chosen for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Questions regarding patient and diagnostic intervals were designed by the study group to match time intervals and events as defined in our adapted version of the standardized definitions proposed by Olesen et al and Weller et al, 5,6 and as published before. 4 The Cancer December 15, 2020 diagnostic interval can be divided further into a primary care, secondary care, and tertiary care interval. All interval lengths were categorical and patient reported (<2 weeks, 2 weeks-1 month, 1-3 months, 3-6 months, 6-12 months, and >12 months).…”
Section: Study Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that a longer total interval worsened OS, while others did not find inferior clinical outcomes. 10 Researchers have argued that this lack of an association, often referred to as the ‘waiting-time paradox’, may be because the studies have not been able to adequately adjust for the aggressiveness of the cancer tumours. The most significant effect of a long interval for sarcomas seems to be the increasing size of the lesion, 12 with consequent decreased chance of uncomplicated resection with clear surgical margins, a greater risk of amputation and increased risk of developing metastases.…”
Section: Introductionmentioning
confidence: 99%